The role of aqp3 in amnion cells exposed to an osmotic stress - Di Paola, Mauricio Adriel (2020)
INTRODUCTION: AQPs in fetal membranes have been proposed to regulate the amniotic fluid volume. Altered expression of these proteins might be associated with oligo and polyhydramnios syndromes. However, we recently observed that the blocking of AQP3 did not prevent cell swelling in amnion cells. In addition, under osmotic stress the pattern expression of amnion AQP3 was different from other AQPs, suggesting a different role for this protein. OBJETIVE: To study the regulation of AQP3 and its role in the amnion.METHODS: Amnion-derived WISH cells were cultured in hypo (150 mOsm) and hyperosmolar (400 mOsm) conditions. Levels of phosphorylated ERK (pERK), JUNK (pJNK) and p38 (p-p38) were studied. Nf-ĸB and tonEBP expressions were assessed in nuclear and cytosolic fractions. AQP3 expression was analyzed after the inhibition of Nf-ĸB and tonEBP pathways with Sodium Salicylate and Cyclosporine-A, respectively. Cell viability was studied by MTT assay. Apoptosis was studied by TUNEL assay and Bax/Bcl-2 ratio after the inhibition of AQP3 using CuSO4 or the specific siRNA. RESULTS: pERK levels increased in hyperosmolarity and did not change in hypoosmolarity (p<0.001; n=6). No significant differences were observed in p-p38 and pJNK (ns; n=6). Nf-ĸB and tonEBP expressions increased in nuclear fraction only in hyperosmolarity (p<0.05; n=5; p<0.01; n=5). In this condition, the blocking of Nf-ĸB pathway increased AQP3 expression (p<0.001; n=5) compared to controls, while the inhibition of tonEBP pathway did not modify its expression. Regarding cell viability in hiperosmolarity, the blocking of AQP3 decreased MTT incorporation (p<0.01; n=8). Moreover, Bax/Bcl-2 ratio and the number of apoptotic nuclei increased after CuSO4 treatment (p<0.001; n=5; p<0.001; n=9) and AQP3 silencing (p<0.05; n=5; p<0.01; n=10).CONCLUSION: Our findings suggest that AQP3 may have an important role in the survival of the amniotic cells and its expression may be regulated by ERK, Nf-ĸB and tonEBP pathways.